Return on Asset dan Investment Opportunity Set dalam Memprediksi Dividend Payout Ratio Perusahaan Manufaktur Sektor Consumer Goods - Moch Fathony (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
Among factors that may be instrumental in affecting the dividend payout decision, this study aims to determine the effect of return on assets (ROA) and investment opportunities on dividend distribution in a company. Using secondary data from 10 Consumer Goods companies listed on the Stock Exchange in the period 2015 - 2019, the data were analyzed using panel regression using EVIEWS. This study found that ROA and investment opportunities can predict the Dividend Payout Ratio in the Consumer Goods Industry. The results suggest that the more profitable a company is, the more likely it is to pay high dividends. Also, high investment opportunities are good position increases a firm's ability to pay dividends.